Phenotypic and genotypic characterization of Aeromonas hydrophila isolated from freshwater fishes at Middle Upper Egypt - Usama H. Abo-Shama; Amany A. Abd El Raheem; Reem M. Alsaadawy; Haitham H. Sayed (Scientific Reports)
Abstract Aeromonas hydrophila is a common fish pathogen and a significant foodborne pathogen of increasing public health concern. This study was conducted in Middle Upper Egypt to determine the prevalence of A. hydrophila among the diseased Oreochromis niloticus (n = 100) and Clarias gariepinus (n = 100) at Assiut and Sohag Governorates. A. hydrophila isolates (n = 44) were assessed for antimicrobial susceptibility and biofilm production. Moreover, PCR was performed to analyze the incidence of some genes in 20 isolates of A. hydrophila. The results showed that 24% and 20% of the examined O. niloticus and C. gariepinus were infected with A. hydrophila respectively, with all (100%) showing a variety of clinical signs of septicemia. A. hydrophila isolates were all biofilm producers, with varied degrees of biofilm production. 79.5% of the isolates were multidrug-resistant and had a high multiple antimicrobial resistance index > 0.2. PCR analysis revealed that all isolates carried act and blaTEM genes but not carried int2 gene. Additionally, sul1, aer, tetA, int1, and qnrA genes were present in 75%, 60%, 55%, 55% and 45% of them, respectively. This study highlights the high incidence of multidrug-resistant pathogenic A. hydrophila in the infected fishes, posing a serious risk to humans and fish.